2021
DOI: 10.3389/fendo.2021.694336
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Nicotine Exposure Induces Low Birthweight and Hyperinsulinemia in Male Rats

Abstract: Smoking during pregnancy is one of the causes of low birthweight. Ingestion of nicotine during pregnancy has various metabolic impacts on the fetus and offspring. According to the developmental origins of health and disease theory, low birthweight is a risk factor for developing various non-communicable diseases, including diabetes. We hypothesized that when nicotine-induced low-birthweight rats, when exposed to a high-fat diet (HFD) after growth, are predisposed to glucose intolerance as a result of a mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…There were no relationships between the quality of ANC, iron supplementation, and maternal smoking status with the incidence of LBW in Central Java (Table 1). (Nemoto et al, 2021). The incidence of LBW in Taiwan was associated with maternal smoking status (OR = 3.46) (Ko et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…There were no relationships between the quality of ANC, iron supplementation, and maternal smoking status with the incidence of LBW in Central Java (Table 1). (Nemoto et al, 2021). The incidence of LBW in Taiwan was associated with maternal smoking status (OR = 3.46) (Ko et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal nicotine exposure caused a decrease in blood IGF-1 levels, similar to prenatal undernutrition, but it is thought that the mechanism is not mediated by miR-322 and GHR, but by some other mechanism. However, LBW model rats exposed to nicotine during the prenatal period also showed elevated blood insulin levels when exposed to a high-fat diet [77]. In other words, LBW, albeit from different causes, has been proven to predispose to the risk of NCDs.…”
Section: Endocrine Feature Of Fetal Undernutritionmentioning
confidence: 99%
“…Small body size rats with LBW and NCG showed increased miR-322 expression and decreased GH receptor expression in the liver, and reduced blood IGF-1 levels. It was shown that the gene was transgenerationally inherited to at least the F4 generation [77]. However, the DNA methylation of miR-322 seen in the F1 generation was not recapitulated in the F2 and later generations, and the mechanism of miR-322 upregulation remains unclear.…”
Section: Animal Models Of Prevention Of Inter-and Transgenerational I...mentioning
confidence: 99%
“…Nicotine is the tobacco compound most highly correlated with metabolic dysfunction in offspring of tobacco addict mothers. Exposure of pregnant mice to nicotine caused several systemic effects in the mother and offspring, including insulin resistance [ 98 , 99 , 100 ]. Robust investigations support that nicotine intake leads to glucocorticoid overexposure in the mother.…”
Section: Nicotinementioning
confidence: 99%
“…It promotes post-translational histones in perivascular adipose tissue and β-cells [ 102 , 103 ]. Recently, it was found that a pre-diabetic state in offspring of nicotine-exposed dams was associated with downregulated transcription factor sterol regulatory element-binding protein-1c (SREBP-1c), peroxisome proliferator-activated receptor-α (PPAR-α), and insulin receptor in the liver [ 99 , 104 ]. SREBP-1c transduces the insulin signal and induces the expression of a family of genes involved in glucose utilization, fatty acid synthesis, and PPAR-α regulates glucose synthesis during fasting states and gluconeogenesis [ 105 ].…”
Section: Nicotinementioning
confidence: 99%